The Colonial Laws of Massachusetts 186 (Rockwell & Churchill 1889) (Passed 1645). - (:unkn) unknown (My University, 1645)
Powder, § 2, MASS ACTS: That no Person (except for the defence of themselves and their vessels at Sea) shall transport any§Gunpowder§out of this jurisdiction, without License first obteined, from some two of the Magistrates, upon penalty of forfeiting all such powder as shall be transporting or transported, or the value thereof;"
Keywords: GUNPOWDER - TRANSPORTATION